The Relationship between HIV Human Immunodeficiency Virus and the Incidence of Tuberculosis (TB) - Misutarno, Misutarno; Hasina, Siti Nur; Shodiq, M.; Khamida, Khamida; Putri, Rahmadaniar Aditya (GLOBAL HEALTH SCIENCE GROUP, 2024)
HIV and Tuberculosis are a deadly combination, these two diseases accelerate the development of each other. The combination of these two infectious diseases influences each other in all aspects of the disease. Objective to determine the relationship between HIV (Human immunodeficiency virus) and the incidence of tuberculosis. Method: to determine the relationship between HIV (Human immunodeficiency virus) and the incidence of tuberculosis. Research methods : The research design used was analytical observational with a cross sectional approach. The population in this study were all HIV sufferers who were undergoing inpatient treatment in the UPIPI Room at Dr. RSUD. Soetomo. The sampling technique uses total sampling. The independent variable in this study is HIV sufferers. The dependent variable in this study is the incidence of tuberculosis. Data analysis used the Spearman Rank test with significance <0.05. Result : The research design used was observational analytics with a cross sectional approach. The population in this study were all HIV sufferers who were undergoing inpatient treatment in the UPIPI Room at Dr. RSUD. Soetomo. The sampling technique uses total sampling. The independent variable in this research is HIV sufferers. The dependent variable in this research is the incidence of tuberculosis. Data analysis using the Rank Spearman test with significance <0.05. Conclusions : Tuberculosis infection in HIV patients is closely related to a decrease in the immune system. As the stage of HIV increases, the body's immune system will decrease, so this can increase the risk of opportunistic infection with tuberculosis. The best way to prevent opportunistic infections is to avoid exposing HIV-infected people to tuberculosis.